Consumers' perceptions about food quality attributes and their incidence in argentinean organic choices - Rodríguez, Elsa Mirta M. (2011)
The objective of this paper is to analyze consumers' perceptions about risk and quality attributes of food consumption; and to evaluate the incidence of these factors when buying organic products in the Argentinean domestic market. Data derives from a food consumption survey on organic and non-organic consumers conducted in Buenos Aires City, Argentina, in April 2005. The Lancaster model (1966) provided the theoretical basis. The results yielded by the estimated logistic model suggest that consumers with higher educational level, who eat healthy food, and consider food control organisms as "inefficient" are more likely to buy organic products. A high percentage of consumers read and trust label information in Argentina. This has interesting policy implications to promote differentiated and high value products, and to reduce information asymmetries.